Disability as an Asset? Reflections on Employment Patterns in the Health and Social Care Sector - Andreassen, Tone Alm (Disability Studies Quarterly, 2012)
The number of people with health problems and disabilities living outside the labor market and on public income security puzzles politicians. The problems associated with having a disability seem to be countered by measures directed either towards people with disabilities (employability programs) or towards employers (anti-discrimination legislation). These problems are at the forefront of many policy discussions. In this article I discuss an alternative perspective, reflecting on whether, in some segments of the labor market, there are dynamics which indicate that disability is an asset, not a liability. I use the Norwegian labor market as the case for this discussion. The proportion of workers with disabilities is higher in the health and social care sector than in the total Norwegian labor market. This overrepresentation of workers with disabilities has remained constant since 2000 and may indicate a particularly unhealthy and impairment-producing sector. This article examines whether this overrepresentation might also indicate that this sector of the labor market considers disability to be an asset – a unique qualification required for certain tasks in the sector. Keywords: disability concepts, labor market, employment, health sector, employer attitudes